Common mechanisms in development and disease: BMP signaling in craniofacial development. (February 2016) - Graf, Daniel; Malik, Zeba; Hayano, Satoru; Mishina, Yuji
Highlights: BMP signaling is one of the key pathways regulating craniofacial development. BMP signaling is involved in the early patterning of the head, the development of cranial neural crest cells, and facial patterning. BMP signaling regulates development of mineralized structures, such as cranial bones, maxilla, mandible, palate, and teeth. Targeted mutations in the mouse have been instrumental to delineate the functional involvement of BMP signaling in different aspects of craniofacial development. Gene polymorphisms and mutations in BMP pathway genes have been associated with various non-syndromic and syndromic human craniofacial malformations. Balanced BMP signaling and its local fine-regulation is critical to organize and maintain craniofacial tissues. This has direct implications for the development of clinical applications using recombinant BMPs or BMP antagonists for tissue engineering in situ. Abstract: BMP signaling is one of the key pathways regulating craniofacial development. It is involved in the early patterning of the head, the development of cranial neural crest cells, and facial patterning. It regulates development of its mineralized structures, such as cranial bones, maxilla, mandible, palate, and teeth. Targeted mutations in the mouse have been instrumental to delineate the functional involvement of this signaling network in different aspects of craniofacial development. Gene polymorphisms and mutations in BMP pathway genes have been associated with various non-syndromic and syndromic human craniofacial malformations. The identification of intricate cellular interactions and underlying molecular pathways illustrate the importance of local fine-regulation of Bmp signaling to control proliferation, apoptosis, epithelial-mesenchymal interactions, and stem/progenitor differentiation during craniofacial development. Thus, BMP signaling contributes both to shape and functionality of our facial features. BMP signaling also regulates postnatal craniofacial growth and is associated with dental structures life-long. A more detailed understanding of BMP function in growth, homeostasis, and repair of postnatal craniofacial tissues will contribute to our ability to rationally manipulate this signaling network in the context of tissue engineering.